Optimasi komposisi briket ramah lingkungan dari limbah batubara sub-bituminus dan karbon rumput laut untuk mengurangi emisi - Sarungallo, Rosalia Sira; Djonny, Maxie; Octovian Dominggus, Reinaldy; Bulo, Lyse; Manukrante, Secwin Sello (Cassowary, 2025)
ABSTRACT: This study investigates the development of environmentally friendly briquettes as a sustainable alternative fuel. Production involved utilizing sub-bituminous coal waste and carbon derived from the carbonization of seaweed. The primary objective of this research was to optimize the briquette composition to achieve optimal combustion performance, with a focus on reducing the emissions of harmful combustion byproducts, such as SOx (sulfur oxides), NOx (nitrogen oxides), COx (carbon oxides), and particulate matter. The results indicate that briquettes with a 1:1 ratio of coal to seaweed carbon, carbonized at 300°C (sample 3A1), demonstrate potential as an alternative fuel. The 3A1 briquettes exhibited a calorific value of 4422 cal/g, with SOx and NOx emissions that were 11.11% and 25.00% lower compared to pure coal briquettes. This reduction is attributed to the lower sulfur and nitrogen content in the seaweed, as well as the improved carbon structure stability resulting from the carbonization process at 300°C. The utilization of coal waste and seaweed in the form of briquettes represents a viable approach to mitigating environmental impacts and contributes to the development of clean and sustainable energy.